The association between human papillomavirus and cervical high‐grade cytology among HIV‐positive and HIV‐negative Tanzanian women: A cross‐sectional study. (16th February 2021) - Swai, Patricia; Kjaer, Susanne K.; Mchome, Bariki; Manongi, Rachel; Msuya, Sia E.; Wu, Chun Sen; Waldstrom, Marianne; Iftner, Thomas; Mwaiselage, Julius; Rasch, Vibeke
Abstract: Introduction: Human papillomavirus (HPV) is the causative agent of precancerous lesions and cervical cancer, cervical cancer being the leading cause of deaths in Tanzanian women. Early detection and treatment of precancerous lesions are important in the prevention of cervical cancer cases. Material and methods: We conducted a cross‐sectional study among 3390 Tanzanian women aged 25‐60 years. Information on lifestyle habits was collected, and women underwent gynecological examination with collection of cervical cells for conventional cytological and HPV testing. Blood samples were tested for HIV. The association between cervical high‐grade cytology (HGC) and potential risk factors was examined using multivariable logistic regression adjusting for age and high‐risk HPV (HR‐HPV). Results: The prevalence of HGC was 3.6% and of low‐grade cytology was 8.3%. In women who were both HR‐HPV‐positive and HIV‐positive, the prevalence of HGC was 28.3%. It increased by age and was 47% among women aged 50‐60 years. Women, who had their sexual debut at age 9‐15 years and 16‐18 years, respectively, had 2.5 and 2.4 times increased odds of HGC compared with women whose sexual debut was at age 21 years and older. HIV‐positive women had increased odds of HGC in comparison with HIV‐negative women after adjustment for age (odds ratio [OR] 2.95, 95% CI 1.92‐4.54). HR‐HPV‐positive women had nearly 100‐fold increased odds of HGC compared with HR‐HPV‐negative women (OR 96.6, 95% CI 48.0‐194), and this estimate was higher among HIV‐positive women (OR 152.2, 95% CI 36.1‐642.0). Conclusions: Increasing age, early age at first intercourse, HR‐HPV, and HIV infections were associated with a substantially increased risk of HGC.